Methylation of SDC2/TFPI2 and Its Diagnostic Value in Colorectal Tumorous Lesions - Zhang, Lianglu; Dong, Lanlan; Lu, Changming; Huang, Wenxian; Yang, Cuiping; Wang, Qian; Wang, Qian; Lei, Ruixue; Sun, Rui; Wan, Kangkang; Li, Tingting; Sun, Fan; et al. (Frontiers in Molecular Biosciences, 2021)
Background: SDC2 methylation is a feasible biomarker for colorectal cancer detection. Its specificity for colorectal cancer is higher than 90%, but the sensitivity is normally lower than 90%. The study aims to improve the sensitivity of SDC2 detection through finding a high positive target from the false negative samples of SDC2 detection based on analysis of the bowel subsite difference in methylation. Methods: Hypermethylated TFPI2 was identified in SDC2 hypomethylated colorectal cancer samples retrieved from TCGA database with methylation level lower than 0.2. Methylation specific PCR assay was developed and then evaluated using tissue samples (184 cancer and 54 healthy control) and stool samples (289 cancer, 190 adenoma and 217 healthy control). Results: TFPI2 was hypermethylated in most SDC2 hypomethylated colorectal cancer samples. when SDC2/TFPI2 combined PCR assay was performed in stool specimens, the AUC value of cancer vs control was 0.98, with the specificity of 96.40% and sensitivity of 96.60%, and the AUC value of adenoma vs control was 0.87, with the specificity of 95.70% and the sensitivity of 80.00%. The improvement in sensitivity was the most momentous in the left colon. As the detection index, Ct value was better in improving the sensitivity of detection than methylation level based on 2-ΔΔCt value. Conclusion: TFPI2 can improve the sensitivity of SDC2 methylation specific detection of colorectal tumorous lesions while maintaining high specificity, in particular reducing the missed detection of left colon cancer and adenoma.